2021
DOI: 10.1038/s41598-021-04029-6
|View full text |Cite|
|
Sign up to set email alerts
|

Data based model for predicting COVID-19 morbidity and mortality in metropolis

Abstract: There is an ongoing need for scientific analysis to help governments and public health authorities make decisions regarding the COVID-19 pandemic. This article presents a methodology based on data mining that can offer support for coping with epidemic diseases. The methodological approach was applied in São Paulo, Rio de Janeiro and Manaus, the cities in Brazil with the most COVID-19 deaths until the first half of 2021. We aimed to predict the evolution of COVID-19 in metropolises and identify air quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Statistical analysis of confirmed COVID-19 data and local meteorological variables in Manaus revealed that low solar radiation cycles may lead to increased COVID-19 deaths due to reduced solar radiation. Dry spells may impair nasal functions that prevent viruses and bacteria from entering the body, leading to increased mortality from COVID-19 [ 47 ]. A study in Italy found that cities with high wind speeds had fewer COVID-19 infections, and inland cities with low wind speeds and high air pollution had higher COVID-19 infections [ 48 ].…”
Section: Results Of the Metrological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of confirmed COVID-19 data and local meteorological variables in Manaus revealed that low solar radiation cycles may lead to increased COVID-19 deaths due to reduced solar radiation. Dry spells may impair nasal functions that prevent viruses and bacteria from entering the body, leading to increased mortality from COVID-19 [ 47 ]. A study in Italy found that cities with high wind speeds had fewer COVID-19 infections, and inland cities with low wind speeds and high air pollution had higher COVID-19 infections [ 48 ].…”
Section: Results Of the Metrological Analysismentioning
confidence: 99%
“…Dry air may impair nasal functions that prevent viruses and bacteria from entering the body, leading to increased mortality from COVID-19. Low solar radiation cycles may lead to higher COVID-19 mortality due to reduced solar radiation [ 47 ]. Rising temperatures could help curb the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers used data mining to study environmental and meteorological variables and determine their correlation with the number of COVID-19 cases in three cities in Brazil. The model they developed was successful in predicting the number of cases and deaths in the cities they studied [ 16 ]. There was plenty of work carried out on predicting the number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge can be treated as the only limitation of the present study, developing the prediction models for COVID-19 cases. Prediction models [37][38][39] that combine several features to estimate the risk of infection have been developed, in the hope of assisting medical staff worldwide in trigging patients, especially in the context of limited health-care resources.…”
Section: Introductionmentioning
confidence: 99%